Second language acquisition : second language systems - Snape, Neal; Kupisch, Tanja (London : Macmillan Education : Palgrave, 2017)
"Exploring canonical topics in second language acquisition, this book introduces a range of theoretical perspectives and investigates the types of research carried out in the field. Written by two experienced researchers and teachers, the textbook takes a modular approach, and is complemented by a range of in-text features that include end-of-chapter questions, concept practice and suggestions for further reading. With its accessible, conversational style, the book is a perfect first introduction for students who are new to this exciting and dynamic field"--Page [4] of cover.
An introduction to linguistic terms -- Acquisition of verbal morphosyntax -- Acquisition of nominal morphosyntax -- A comparison between UG and non-UG frameworks -- Phonology -- Simultaneous bilingualism.
Includes bibliographical references (pages 215-238) and index.
Keywords: Second language acquisition